EVOLUSI DAN TANTANGAN KEAMANAN DAN KERAHASIAAN REKAM MEDIS BERDASARKAN HAK AKSES DI RUANG PENYIMPANAN PADA ERA DIGITALISASI RUMAH SAKIT “X” - Nur Maimun; Ulil Kholili; Jihan Natassa; Sri Wardani; Haryani Octaria (LPPM Universitas Awal Bros, 2026)
The advancement of information technology has driven the transformation of medical record systems from paper-based records to Electronic Medical Records (EMRs). The implementation of EMRs provides various benefits, including improved operational efficiency, data accessibility, and healthcare service quality. However, digitalization also presents challenges related to patient data confidentiality and security, including the risks of data breaches, unauthorized access, and cyberattacks. This study aims to explore the evolution and challenges of medical record confidentiality in storage systems during the digitalization era. A qualitative research method with a phenomenological approach was employed. Informants were selected using a non-probability sampling technique through purposive sampling. The results showed that, from the man aspect (human resources), the competence and readiness of personnel in maintaining the security and confidentiality of medical records were adequate, although the availability of information technology personnel remained insufficient. From the money aspect, funding requirements for maintaining the security and confidentiality of medical records were proposed through the hospital planning department. Regarding the material aspect, the facilities and infrastructure supporting EMR implementation at X Hospital Pekanbaru were almost fully available. From the method aspect, the hospital had established standard operating procedures (SOPs) related to electronic medical records. Meanwhile, the machine aspect indicated that the implementation of technology and equipment supporting the security and confidentiality of medical record data, both manual and electronic, had been carried out relatively well. Therefore, strengthening information technology human resources, enhancing staff capacity, and continuously optimizing digital security systems are recommended to maintain the confidentiality and security of medical record data in the digital era.